Comparing peaceful mindsets among drug addiction clients in differentRehabilitation contexts - Hendiani, Nurlita; Saputra, Wahyu Nanda Eka; Handaka, Irvan Budhi; Supriyanto, Agus (Universitas Islam Negeri Raden Intan Lampung, 2026)
Throughout the rehabilitation program, addicted clients are assisted by addiction counselors to develop a peaceful mindset to aid recovery. However, addicted clients experience cognitive and psychological difficulties as the factual and theoretical gaps related to the formation of a peaceful mindset with two aspects (inner peace and internal harmony). So, this study aims to analyze the peaceful mindset profile of addiction clients, including inner peace and internal harmony, as important aspects of the psychological, spiritual, and social recovery process. A comparative design on 112 addiction clients from three rehabilitation institutions in the Special Region of Yogyakarta. Measurements using the peace mindset scale (which has validity and reliability). Data analysis using descriptive statistics and ANOVA. Peaceful mindset of addiction clients through two aspects (inner peace and internal harmony) at various rehabilitation locations. The results of the peaceful mindset categorization show that there are addiction counseling clients in the low and very low categories who require intensive assistance. The ANOVA test revealed significant differences between locations with F=118.288 (p=0.000) for inner peace and F=129.049 (p=0.000) for internal harmony. A comparison between locations shows that drug rehabilitation in rehabilitation centers has a significantly lower peaceful mindset score than both prisons, while the two prisons show no significant difference. These findings confirm that program structure, intensity of assistance, and quality of psychospiritual counseling by the counselor have an important influence on the inner stability of addiction clients. Developing a spiritual counseling model could improve the inner peace and harmony of addiction clients.